2014
DOI: 10.1186/1471-2156-15-22
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic parameters for yield, plant growth and cone chemical traits in hop (Humulus lupulus L.)

Abstract: BackgroundMost traits targeted in the genetic improvement of hop are quantitative in nature. Improvement based on selection of these traits requires a comprehensive understanding of their inheritance. This study estimated quantitative genetic parameters for 20 traits related to three key objectives for the genetic improvement of hop: cone chemistry, cone yield and agronomic characteristics.ResultsSignificant heritable genetic variation was identified for α-acid and β-acid, as well as their components and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 65 publications
1
15
0
1
Order By: Relevance
“…Recent genetic, genomic, and quantitative trait analyses have demonstrated that the genome of hop is complex and structurally diverse (Zhang et al, 2017 ). Irregularities in hop transmission genetics are reflected in non-Mendelian segregation distortion and sex ratio bias (Seefelder et al, 2000 ; Jakse et al, 2008 , 2011 ; McAdam et al, 2013 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic, genomic, and quantitative trait analyses have demonstrated that the genome of hop is complex and structurally diverse (Zhang et al, 2017 ). Irregularities in hop transmission genetics are reflected in non-Mendelian segregation distortion and sex ratio bias (Seefelder et al, 2000 ; Jakse et al, 2008 , 2011 ; McAdam et al, 2013 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed this has been the case for various essential oil crops over the past decades. For example, five cycles of recurrent selection in Cymbopogon flexuosus (Lemongrass) increased mean oil concentration from 0.7 to 1.7 % (Kulkarni et al 2003), Barton et al (1991) H. lupulus Hop 0.37 0.03 Murakami (1999), McAdam et al (2014) while in Carum carvi (Annual Caraway) mean oil concentration increased from 3.4 to 7.4 % over 20 years of recurrent selection (Pank 2010). The Australian Tea Tree breeding program has doubled commercial Tea Tree oil yield from 150 to 300 kg ha −1 since 1993 through selection based on a weighted multi-trait index (Baker et al 2014).…”
Section: Selecting For Essential Oil Yieldmentioning
confidence: 98%
“…A produtividade e a composição química de uma cultura é definida pela interação O desempenho no cultivo do lúpulo, é dependente principalmente de aspectos como produção de cones por planta, juntamente as características químicas da produção de resinas, contendo alfa e beta ácidos que conferem o amargor e aroma a cerveja (HIERONYMUS, 2012). Os teores de alfa e beta ácidos podem variar de plantas da mesma variedade com idade diferente e entre locais de plantio distintos, demostrando ser um caráter de origem complexa, de baixa herdabilidade e sofrendo alta influência do ambiente (MCADAM et al, 2014 chegou a uma definição oficial sobre seu significado:…”
Section: Reflexo Da Interação Genótipo Ambiente No Cultivo Do Lúpulounclassified